A Novel Viewpoint on the Anticipatory Postural Adjustments During Gait Initiation - Farinelli, Veronica; Bolzoni, Francesco; Marchese, Silvia Maria; Esposti, Roberto; Cavallari, Paolo (Frontiers in Human Neuroscience, 2021)
Anticipatory postural adjustments (APAs) are the coordinated muscular activities that precede the voluntary movements to counteract the associated postural perturbations. Many studies about gait initiation call APAs those activities that precede the heel-off of the leading foot, thus taking heel-off as the onset of voluntary movement. In particular, leg muscles drive the center of pressure (CoP) both laterally, to shift the body weight over the trailing foot and backward, to create a disequilibrium torque pushing forward the center of mass (CoM). However, since subjects want to propel their body rather than lift their foot, the onset of gait should be the CoM displacement, which starts with the backward CoP shift. If so, the leg muscles driving such a shift are the prime movers. Moreover, since the disequilibrium torque is mechanically equivalent to a forward force acting at the pelvis level, APAs should be required to link the body segments to the pelvis: distributing such concentrated force throughout the body would make all segments move homogeneously. In the aim of testing this hypothesis, we analyzed gait initiation in 15 right-footed healthy subjects, searching for activities in trunk muscles that precede the onset of the backward CoP shift. Subjects stood on a force plate for about 10 s and then started walking at their natural speed. A minimum of 10 trials were collected. A force plate measured the CoP position while wireless probes recorded the electromyographic activities. Recordings ascertained that at gait onset APAs develop in trunk muscles. On the right side, Rectus Abdominis and Obliquus Abdominis were activated in 11 and 13 subjects, respectively, starting on average 33 and 54 ms before the CoP shift; Erector Spinae (ES) at L2 and T3 levels was instead inhibited (9 and 7 subjects, 104 and 120 ms). On the contralateral side, the same muscles showed excitatory APAs (abdominals in 11 and 12 subjects, 27 and 82 ms; ES in 10 and 7 subjects, 75 and 32 ms). The results of this study provide a novel framework for distinguishing postural from voluntary actions, which may be relevant for the diagnosis and rehabilitation of gait disorders.